Meningkatkan Keterampilan Dasar Mengajar Guru Melalui Pelaksanaan Supervisi Akademik Kenjungan Kelas Pada Guru-Guru Di SD Negeri 050767 Perkebunan Serapuh Tahun Pelajaran 2019/2020 - Hasnah Hasnah (Universitas Islam Sumatera Utara, 2022)
This study aims to improve the basic teaching skills of teachers in the classroom in carrying out tasks at SD Negeri 050767 Perkebunan Serapuh for the 2019-2020 Academic Year in order to improve the quality of learning carried out by teachers every meeting to students in the classroom. This type of research is School Action Research (PTS). The results of the first cycle research can be seen that the basic teaching skills of teachers at SD Negeri 050767 Perkebunan Serapuh in cycle I get the Less category with an average percentage of 57.3%. Then the results of the second cycle of research can be seen that the basic teaching skills of teachers at SD Negeri 050767 Perkebunan Serapuh get the Good category with a percentage of 80.6%. Based on the results of the first and second cycle research, it can be concluded that the basic teaching skills of teachers in SD 050767 Perkebunan Serapuh can improve after academic supervision of class visits.